A novel single-stage PWM microinverter topology using two-power switches - A. Razi; M. Nabil Hidayat; M. N. Seroji; S. Z. Mohammad Noor (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents a novel single-stage Microinverter topology using only two-power switches. The number of components count are directly proportional to the power losses, weight, cost and complexity of the design. Nowadays, conventional Microinverter without transformer having minimum of six power switches, while only three power switches involved in a Microinverter structure with the presence of a transformer. Thus, this paper proposed a novel Microinverter topology with only two-power switches to convert DC-voltage from Photovoltaic (PV) module to an AC-output. Modes of operation and current flow during each cycle are being explained. Variation of modulation index, irradiance and temperature of the PV module, the switching frequency and harmonic content of the proposed Microinverter are being analysed. A simulated model of Microinverter topology, employed only two power switches with a standard Unipolar Sinusoidal Pulse Width Modulation (SPWM) having 0.85% harmonic percentage; able to inject current to the load; have been successfully built and demonstrated through simulation based on MATLAB/Simulink, thus provide theoretical validation for further research.